The structure and distribution of coral reefs being the first part of the geology of the voyage of the Beagle, under the command of Capt. Fitzroy, R.N. during the years 1832 to 1836 - Darwin, Charles 1809-1882 (Cambridge library collection. Life sciences, 2013)
Published in 1842, this important monograph by Charles Darwin (1809-82) formed the first part of a trilogy of geological studies based on observations made during the celebrated second voyage of the Beagle. Influenced by Charles Lyell's Principles of Geology, Darwin drew in particular on data from the survey of the Keeling Islands in the Indian Ocean to support his theory that subsidence of the ocean floor can account for the formation of coral atolls. He first presented his findings in a paper for the Geological Society of London in 1837, but a heavy workload and illness delayed the appearance of this elegantly argued and illustrated study. For this and his work on barnacles, Darwin would receive the Royal Society's royal medal in 1853. The other studies in the trilogy, Geological Observations on the Volcanic Islands (1844) and Geological Observations on South America (1846), are also reissued in this series.